If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -6c = (-37) 5 + -6c = -37 Solving 5 + -6c = -37 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6c = -37 + -5 Combine like terms: 5 + -5 = 0 0 + -6c = -37 + -5 -6c = -37 + -5 Combine like terms: -37 + -5 = -42 -6c = -42 Divide each side by '-6'. c = 7 Simplifying c = 7
| m=-4,(8,9) | | 7x-43+147-3x=90 | | 2x^3+54x= | | 3d+4=2+36-0.5 | | A(25)=A(9)+(8) | | -3=-1.5+0.5y | | 5x+3x=4x+2 | | 169x^4-196y^6= | | 0.3(30)+.15x=.2(30+x) | | 5x^2+12x-7=0 | | (w-11)w=180 | | 9x-8+3x+6= | | 5x+3x=4x-2 | | 9x^6+21x^3+10= | | 3x*5=3x | | 60+50+x+70=180 | | -8.1(-10.7)= | | -8-(-10.7)= | | -4x+9z=9z+6-3z | | (x^2-36)3=80 | | 4x^2+2xy-6y^2= | | 7(2)+2y=4 | | 2x^2+2y^2-12x-24y+10=0 | | 4u=35-3u | | (4x+34)+(x+36)=180 | | 2x+3(x-1)=4x-25+2x | | 3x^2+-36X+28=0 | | -8z+4z=z+2+7z | | 7(p+7)+p=81 | | 8x-6=8+7x | | -6(x+5)=-6x-36 | | -4+-1B+8x+-2xB=0 |